Factors Affecting English Teachers’ Implementation of Active Learning: A Case from Ethiopia - Addisu, Mulugeta; Regassa, Taye (Universitas Muhammadiyah Yogyakarta, 2026)
Background: The Ethiopian Ministry of Education introduced active learning into the education system because the traditional teacher-centered method effectively limited students’ target-language learning. However, teachers still dominate most of the instructional process, and students remain passive listeners. Objective: This study aims to investigate factors affecting the implementation of active learning by secondary school English teachers in North Shoa Zone, Oromia, Ethiopia. Methods: A descriptive survey research design using a mixed-methods approach was employed. The study participants were 72 English teachers teaching grades 11 and 12 across 15 public schools. Data were collected through questionnaires, interviews, and classroom observations. The data collected through questionnaires were analyzed using descriptive statistics, including mean and standard deviation, in SPSS. Conversely, data obtained through interviews and observations were analyzed thematically. Finally, the data were merged and interpreted side-by-side. Findings: The findings revealed student-related challenges, including limited language proficiency, a lack of interest, and fear of class discussion. The result also showed that resource-related factors, including large class sizes, fixed seating arrangements, insufficient instructional time, and teachers’ tendency to use teacher-centered methods, posed major challenges to the effective implementation of active learning. Conclusion: The findings indicated that although active learning has been introduced into the education system, its implementation remains partial due to various factors that impede its effective implementation. Therefore, teachers should shift their teaching methods from teacher-centered to active learning. Furthermore, to improve the successful implementation of active learning, stakeholders should address the identified challenges by providing adequate resources and support.